TG2 regulates the heat‐shock response by the post‐translational modification of HSF1. (11th May 2018) - Rossin, Federica; Villella, Valeria Rachela; D'Eletto, Manuela; Farrace, Maria Grazia; Esposito, Speranza; Ferrari, Eleonora; Monzani, Romina; Occhigrossi, Luca; Pagliarini, Vittoria; Sette, Claudio; Cozza, Giorgio; Barlev, Nikolai A; et al.
Abstract: Heat‐shock factor 1 (HSF1) is the master transcription factor that regulates the response to proteotoxic stress by controlling the transcription of many stress‐responsive genes including the heat‐shock proteins. Here, we show a novel molecular mechanism controlling the activation of HSF1. We demonstrate that transglutaminase type 2 (TG2), dependent on its protein disulphide isomerase activity, triggers the trimerization and activation of HSF1 regulating adaptation to stress and proteostasis impairment. In particular, we find that TG2 loss of function correlates with a defect in the nuclear translocation of HSF1 and in its DNA‐binding ability to the HSP70 promoter. We show that the inhibition of TG2 restores the unbalance in HSF1‐HSP70 pathway in cystic fibrosis (CF), a human disorder characterized by deregulation of proteostasis. The absence of TG2 leads to an increase of about 40% in CFTR function in a new experimental CF mouse model lacking TG2. Altogether, these results indicate that TG2 plays a key role in the regulation of cellular proteostasis under stressful cellular conditions through the modulation of the heat‐shock response. Synopsis: TG2, through its protein disulphide isomerase activity, triggers the trimerization and activation of HSF1. The inhibition of TG2 restores the unbalance in HSF1‐HSP70 pathway in cystic fibrosis indicating that TG2 plays an important role in the regulation of cellular proteostasis under stressful cellular conditions through the modulation of the heat shock response. The protein disulphide activity of TG2 post‐translationally modifies HSF1. TG2, by activating HSF1, regulates HSP70 protein expression. TG2 favour the degradation of mutant CFTR via the HSF1/HSP70 pathway. Abstract : TG2 triggers the trimerization and activation of HSF1 dependent on its disulphide isomerase activity. The inhibition of TG2 restores the unbalance in the HSF1‐HSP70 pathway in cystic fibrosis indicating a role for TG2 in the regulation of cellular proteostasis under stress.